Reconstruction Of Martin Heiddeger's Thinking Existentialism Model on Education inThe Industrial Era 4.0 - M. Solikul Hadi; Muhammad Nuril Anam; M. Sayyidul Abrori (Journal of Research in Islamic Education, 2021)
The industrial revolution 4.0 is an early sign of a digital era. The developments and anxieties of the 21st century are very diverse. Whether we admit it or not, the 21st century provides everything that goes beyond human limits, but also creates a paradoxical phenomenon with the reality of life with so much market competition. Starting from biotic competition, technology competition, food competition and weapons competition. The industrial revolution 4.0 stipulates that humans cannot live without being accompanied by technology. Starting from shopping, ordering food, paying bills, and things related to other human activities, even in the world of education. That is the outline of the face of the majority of the industrial revolution 4.0 community in the 21st century. With all the progress of the industrial revolution 4. 0 is described as fiber with excitement but poor in enlightenment, so much information but poor in contemplation and socialization, and so much pleasure but poor in peace. So with the philosophy offered by Martin Heidegger with an existential approach model, it needs to be reconstructed by being developed in the era of the industrial revolution 4.0 where humans understand and understand their existence on the world stage or even they are able to be involved in everything around them.